Fused Deposition Modelling of Wood-Plastic Composites: Materials, Processes, and Future Directions - Wan Harun, Wan Sharuzi (Journal of Composites and Biodegradable Polymers, 2025)
Fused Deposition Modelling (FDM) of Wood-Plastic Composites (WPCs) offers a compelling pathway towards sustainable manufacturing. However, the progression from prototyping to functional components is governed by a fundamental conflict: the pursuit of high wood content for sustainability directly opposes the thermo-rheological constraints of the extrusion process. This review critically analyses this conflict, arguing it is the primary source of the two main defects that limit structural applications: severe mechanical anisotropy from weak interlayer adhesion, and multi-scale porosity inherent to both the feedstock and the printing process. By deconstructing the material systems and process-structure-property relationships, this review synthesises current strategies to mitigate these challenges. Ultimately, this review argues that the future of the field depends on a paradigm shift towards intelligent manufacturing, integrating predictive modelling with novel bio-based materials and leveraging the unique properties of WPCs for functionally graded components and environmentally responsive 4D printing.